2014
DOI: 10.1111/jhn.12192
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review investigating associations between parenting style and child feeding behaviours

Abstract: Parenting styles showed only weak to moderate associations with individual domains of child feeding. The most consistent relationship found was a negative association between permissive parenting and monitoring for both mothers and fathers in two studies. Progress in this field could be achieved by conducting studies targeting fathers and culturally diverse populations, and development of a tool which could reflect overall child feeding behaviour rather than individual domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 43 publications
2
67
1
3
Order By: Relevance
“…It is also possible that there are no substantive differences between EAH relationships for different parent feeding practices or different parenting styles (please see regression coefficients and confidence intervals in Tables 3 and 4). Future studies should examine other unmeasured variables that may potentially contribute to variance in this study, such as child temperament (Anzman & Birch, 2009; C. Collins, Duncanson, & Burrows, 2014), adrenocortical regulation (Francis, Granger, & Susman, 2013), neurobiological activation of reward pathways (Born, et al, 2010), and genetics (Fisher, Cai, et al, 2007; Provencher, et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that there are no substantive differences between EAH relationships for different parent feeding practices or different parenting styles (please see regression coefficients and confidence intervals in Tables 3 and 4). Future studies should examine other unmeasured variables that may potentially contribute to variance in this study, such as child temperament (Anzman & Birch, 2009; C. Collins, Duncanson, & Burrows, 2014), adrenocortical regulation (Francis, Granger, & Susman, 2013), neurobiological activation of reward pathways (Born, et al, 2010), and genetics (Fisher, Cai, et al, 2007; Provencher, et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that parental control is not usually isolated to the feeding environment, but instead typically reflects a wider style of parenting (see Collins, Duncanson & Burrows, 2014, for a review). For example, an authoritarian parenting style is characterised by high demand and control over their child, and this type of parenting style has been linked with excessive levels of pressure and restriction over their child in the feeding domain (e.g., Hughes, Power, Fisher, Mueller & Nicklas, 2005).…”
Section: Figures 5 and 6 About Herementioning
confidence: 99%
“…Theoretical models including the Ecological Model (Bronfenbrenner, 2009) posit the role of family members in individuals’ dietary intake/behaviors; however, most research has focused on how family and parental factors influence children’s outcomes (Collins, et al, 2014; Mazarello Paes, et al, 2015; Pinquart, 2014). For example, even though a well-established literature suggests that children regularly influence their parents’ food-purchasing behaviors (Atkin, 1978; Gaumer & Arnone, 2009; Turner, et al, 2006; Wingert, et al, 2014), few studies have examined how child-related factors impact their parents’ health practices and outcomes (Fisher, 2006).…”
Section: Introductionmentioning
confidence: 99%